Case Report: A spinal infection with bilateral psoas abscesses was treated with NPWT to enhance the local infection by increasing the infiltration of neutrophil cells and draining the pus - Jianhua Li; Zhengqi Chang (Frontiers in Cellular and Infection Microbiology, 2023)
Treatment of spinal brucellosis with bilateral psoas abscess is a challenging clinical endeavor. We retrospectively evaluated a case of lumbar infection and bilateral psoas abscess, and was effectively managed through a unilateral extreme lateral approach with the aid of NPWT for bilateral drainage. We hypothesize that NPWT can influence the Piezo1 receptor of neutrophils and further influence the interaction between neutrophils and endothelial cells to promote the clearance of infected lesions, and this phenomenon is also observed in pathological slides. This proves that NPWT can rapidly enhance the recruitment of neutrophils in the infected area and improve the local immune response, and after a year of reassessment and tracking, Bilateral drainage using NPWT via a unilateral Extreme Lateral Approach could acquire satisfactory surgical outcomes, can be used as a treatment modality for lumbar infection with bilateral psoas abscesses.